On dependability evaluation of fieldbus networks: a permanent fault analysis - Adriano da Silva Carvalho (2001)
The paper focus dependability modelling and evaluation of fieldbus networks in the presence of permanent faults. Several architectures are analysed, considering different operating modes, topologies and fault types. Two measures of dependability are evaluated: reliability and asymptotic unavailability. The aim is to compare these various design solutions, to define essential parameters and to study their effects on fieldbus dependability.